Gerakan Bersama Pentingnya Antisipasi Gizi Buruk dan Stunting (Gema Pentas) Melalui Edukasi Pentingnya 1000 Hari Pertama Kehidupan di Desa Sukaraharja Kabupaten Ciamis - Tira Seyudhianti; Sunartono, Sunartono; Monalisa, Dian (Journal of Health Innovation and Community Services, 2025)
Background: The community service activity carried out was a joint movement emphasizing the importance of anticipating malnutrition and stunting. Objective: The community service activity aimed to increase the knowledge of parents of toddlers regarding the first 1000 days of life and good nutritional behavior changes so as to improve the health and nutritional status of children. Method: This activity is in the form of direct counseling using leaflets designed by the Community Service Team. Pre and post tests are carried out before and after the educational activities to determine the effectiveness of the education implemented. Furthermore, participatory monitoring and evaluation are carried out by inviting residents, cadres, and village officials to conduct periodic evaluations (3–6 months) to monitor the impact of education and nutritional improvements. Results: The community service activity received enthusiastic participation from pregnant women and mothers of infants, with improved knowledge evident from the pre-test results before the educational material was provided and the post-test results afterward. The community service activity lasted approximately 60 minutes and was accompanied by village midwives and community health workers. The activity agenda began with an opening, team introductions, explaining the activity objectives, presenting the material, and concluding with an evaluation. Conclusion: The increased proportion of participants demonstrating adequate knowledge following the educational intervention reflects its effectiveness. Statistical analysis confirmed that the observed change was statistically significant.